2003
DOI: 10.1097/01.mp.0000068235.45178.c1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of Galectin-3 and the Macrophage Migration Inhibitory Factor (MIF) in Human Colorectal Cancers

Abstract: In conclusions, MIF and galectin-3 expression levels in colorectal tumors are related to their levels of biological aggressiveness. These markers could be used to identify patients at risk, for whom more aggressive adjuvant therapy seems to be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 51 publications
8
63
1
Order By: Relevance
“…We did, however, not observe significant differences in the intensity of expression between lowand high-grade tumours and not in dependence on the disease-free survival, although a prolonged disease-free survival was accompanied by a slight, statistically non-significant reduction in the mean intensity of expression (1.43) as compared to metastasis developing concomitantly with the primary tumour (mean intensity: 1.73). Other studies revealed either similar results or reported upregulation of galectin-3 expression during tumour progression (Andre et al, 1999;Nakamura et al, 1999;Legendre et al, 2003Endo et al, 2005). Particularly one of the latter studies performed a highly sophisticated quantitation of galectin-3 expression .…”
Section: Discussionsupporting
confidence: 66%
“…We did, however, not observe significant differences in the intensity of expression between lowand high-grade tumours and not in dependence on the disease-free survival, although a prolonged disease-free survival was accompanied by a slight, statistically non-significant reduction in the mean intensity of expression (1.43) as compared to metastasis developing concomitantly with the primary tumour (mean intensity: 1.73). Other studies revealed either similar results or reported upregulation of galectin-3 expression during tumour progression (Andre et al, 1999;Nakamura et al, 1999;Legendre et al, 2003Endo et al, 2005). Particularly one of the latter studies performed a highly sophisticated quantitation of galectin-3 expression .…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, MIF was identified as a miR-451 target with the bioinformatic prediction program miRBase Targets. 9 We decided to study MIF further, as the overexpression of MIF has been observed in several human neoplasms (31,32), including gastric (33) and colorectal cancer (34), and has been shown to exert effects on a variety of cell types by regulating diverse biological processes. The observed effects include inflammation, immune regulation, physiologic and pathophysiologic neovascularization, and cell replication.…”
Section: Resultsmentioning
confidence: 99%
“…It is a unique cytokine affecting multiple processes fundamental to tumorigenesis (Bach et al, 2009). In addition, MIF has prognostic value in human colorectal cancer because its expression correlates with aggressiveness of the cancer (Legendre et al 2003). MT2A gene belongs to the metallothionein families, which are important for metal ion homeostasis.…”
Section: Discussionmentioning
confidence: 99%